Integrasi CRM-B2B - Wismantoro Yohan (Semantik, 2011)
ABSTRACT: Customer relationship management (CRM) and business-to-business (B2B) are essential to the success of modern business. Althoughthey are two different modules, they shere many similaritas. The integration of CRM and B2B will benefit all related parties in business processes, including sales,marketing,customer service, and information support. This article disucusses the characteristic, similarities, and differences of B2B from CRM. It alsoexplores the CRM_B2B integration strategise, the current issues, and their future development trends.Keyword: business, customer relationship, marketing strategis